Checkpoint inhibitor‐associated bullous cutaneous immune‐related adverse events: a multicentre observational study. (1st December 2022) - Kawsar, Anusuya; Edwards, Charlotte; Patel, Pooja; Heywood, Richard M.; Gupta, Aakriti; Mann, Jasmine; Harland, Christopher; Heelan, Kara; Larkin, James; Lorigan, Paul; Harwood, Catherine A.; Matin, Rubeta N.; et al.
Abstract: Background: Checkpoint inhibitor (CPI) therapy has significantly improved overall survival in several cancers including metastatic melanoma (MM) and in the adjuvant setting. Cutaneous immune‐related adverse events (irAEs) secondary to CPIs are commonly observed; however, autoimmune blistering disorders such as bullous pemphigoid (BP) are rare. Objectives: To review the prevalence, incidence risk, clinicopathological features and management of toxicity in bullous cutaneous irAEs associated with CPI therapy. Methods: A multicentre, retrospective, observational study of CPI‐associated bullous irAEs in adults with all cancers across four UK specialist centres between 2006 and 2019. Results: In total, 7391 patients were identified. CPI‐associated bullous irAEs including BP (n = 16) occurred in 0·3% (n = 22). The median age of onset was 76 years, and there was a male predominance. Most patients had cutaneous melanoma (73%, n = 16), of which 81% (13 of 16) were BRAF wildtype. Grade 1, 2, 3 and 4 skin toxicity occurred in 9%, 45%, 41% and 5%, respectively. The mucosae were involved in 27%, and 25% of confirmed cases of BP did not present with bullae. The median time to onset of bullous irAEs was 12 months, with a median total symptom duration of 6 months. Single PD‐1/PD‐L1 agents had a longer time to onset of symptoms than combination therapy (median 12 vs. 7 months, respectively). Overall, 91%, 64% and 9% of patients required one, two or three lines of treatment, respectively. Two cases occurred after completion of CPIs (1 and 3 months). Of the 20 cases that presented while on CPIs this was permanently discontinued in 55% (11 of 20) and temporarily held in 20% (four of 20). In the four held cases of CPI, bullous eruption reflared in 50%. Conclusions: CPI‐associated bullous skin toxicity is a rare cutaneous irAE occurring in approximately 0·3% of cases over 13 years of treated patients in this series. Not all cases are diagnostic of BP, but management remains the same. There is a prolonged latency of onset compared with other cutaneous irAEs, with a median time of 12 months, and they can occur after cessation of therapy. Discontinuation of CPIs may be required. Recognizing bullous irAEs promptly and referral to dermatology are essential to optimize management and improve patient outcomes and tumour responses. What is already known about this topic? Checkpoint inhibitor (CPI)‐associated bullous pemphigoid is a rare dermatological immune‐related adverse event (irAE) that has been reported in small case series and reports. What does this study add? This is the largest multicentre, observational study conducted in the UK over the longest period of 13 years, which demonstrates an overall incidence of bullous cutaneous irAEs secondary to CPIs of 0·3%. Clinical presentation is variable, with one‐quarter of patients with bullous pemphigoid presenting without bullae, and mucosal involvement was noted in 27%. Prolonged pruritus is frequently a prodromal symptom. The median time to diagnosis is 12 months and irAEs rarely present after cessation of treatment. Time to onset of symptoms is longer with a single CPI, but with a shorter duration of symptoms compared with combination CPI therapy. Most patients had cutaneous melanoma, of which 81% were BRAF wildtype. Abstract: This is the largest multicentre, observational study conducted in the UK, demonstrating an overall incidence of bullous cutaneous irAEs associated with CPI of 0·3%. Clinical presentation may vary, with pruritus and non‐bullous variants appearing similar to other cutaneous toxicities. Time to onset appears later than with other cutaneous toxicities (12 months) and can occur after discontinuation of therapy. Interruption of CPI is often needed. Our study demonstrates this occurs mostly in men, older age groups and is associated with BRAF wildtype in MM patients. It is important for clinicians to recognize this condition promptly, so early optimal management is initiated to reduce interruptions to CPI and improve overall patient outcomes and tumour response. Linked Comment: K. Kridin and C.M. Hammers. Br J Dermatol 2022; 187:843–844 . Plain language summary available online